Kompetensi Guru dan Ketepatan Pemilihan Metode Pembelajaran Berpengaruh Terhadap Hasil Belajar Siswa di SMK Untung Surapati Pasuruan - Defri Maulana; Sugeng Pradikto (Student Research Journal, 2025)
This study aims to analyze the influence of teacher competence and the accuracy of teaching methods on student learning outcomes at SMK Untung Surapati Pasuruan. Teacher competence, including pedagogical, professional, social, and personal competencies, is considered crucial in creating an effective learning process. The accuracy of teaching methods is also examined to determine the extent to which selecting methods suitable to students' characteristics and lesson materials affects their understanding and engagement. This research employs a quantitative approach with a 2x2 factorial design, involving 67 students selected through proportional random sampling. Data were collected via questionnaires and tested for validity and reliability to ensure accuracy and consistency. The findings reveal that both teacher competence and teaching methods significantly influence student learning outcomes. The combination of these factors positively impacts the enhancement of students' cognitive, affective, and psychomotor aspects. Therefore, teachers are encouraged to continually improve their competence through training and further education and to choose teaching methods that align with students' needs to achieve optimal learning.